POLA PEMBERIAN ANTIBIOTIKA UNTUK PASIEN COMMUNITY ACQUIRED PNEUMONIA ANAK DI INSTALASI RAWAT INAP RSUD BULELENG TAHUN 2013 - Made Virgo Baharirama; I Gusti Ayu Artini (E-Jurnal Medika Udayana, 2017)
Community acquired pneumonia is an infectious disease that very common and cause high number of deaths among children under five years old in developing countries, especially in Indonesia. Therefore, this study was conducted to determine the pattern of antibiotics treatment for patients with community acquired pneumonia in children at Instalasi Rawat Inap Rumah Sakit Umum Daerah Kabupaten Buleleng in 2013. The design of this study is a descriptive observational study with cross-sectional approach. The subjects are all children patients with community acquired pneumonia from June to September 2013 at Instalasi Rawat Inap Rumah Sakit Umum Daerah Kabupaten Buleleng which selected by total sampling method and analyzed by descriptive statistics. From 77 samples were obtained, the class of antibiotics that are given are third generations of cephalosporin, such as intravenous Cefotaxime (96.1%) and intravenous Ceftriaxone (3.9%). It can be concluded that the treatment of choice for community acquired pneumonia patients in children at Instalasi Rawat Inap Rumah Sakit Umum Daerah Kabupaten Buleleng in 2013 is cefotaxime.